Proyecto de factibilidad para la creación de una empresa de servicio de lavado automático de prendas de vestir para el canton Yantzaza, en la provincia de Zamora Chinchipe - Jaramillo Torres, Luli Gisela (2017)
The canton Yantzaza is now a tourist power, and is the economic center of the province because of the migration of people from other cities, which have achieved a great development for the canton: most inhabitants, Benefit from this migration and reception of tourists and opt to undertake a sustainable business according to the needs of the population and thus compensate their economy. The insertion of women into society has led to the integral development of families due to equal opportunities and rights, so the economy in each household is balanced favorably. The present thesis work has as main objective to realize a FEASIBILITY PROJECT FOR THE CREATION OF A COMPANY OF SERVICE OF AUTOMATIC WASHING OF CLOTHES OF DRESSING FOR THE COUNTRY YANTZAZA, IN THE PROVINCE OF ZAMORA CHINCHIPE, after the fulfillment of general objectives as they are: The market study, technical study, organizational study, economic study and financial study, procedures that will define the feasibility of the implementation of the company in the market. In order to carry out the market study, information was obtained through surveys, which were applied to 370 people, specifically female heads of household. This result led to the delimitation of the sample, taking into account the number of inhabitants that for the base year 2015 Are 19989.77 inhabitants and four members per family. The results of the survey allowed us to define a potential demand of 4997.4 families that could use the service, a real demand of 2553.7 families that currently use the service and an effective demand of 2374.9 families that are willing to use the service which gives an effective demand 177,788.85 kg and annual taking into account the per capita consumption that is 136.51 kilograms. A survey was also applied to the businesses involved in this activity and the results yielded an annual supply of 18987 kg annually, which can calculate an unsatisfied demand of: 158,801.85 kg annually. In the development of the technical study the macro and micro location for the project location was defined, which is in the Centro neighborhood between Iván Riofrio and Primero de Mayo streets, Yantzaza canton of the province of Zamora Chinchipe of the Republic of Ecuador. In terms of installed capacity is 159,744.0 kg per year, but considering the working hours, delay times and specifications of use of the machines, the maximum capacity used will be 33% in terms of the package entered and with 5 shifts approximately per machine In terms of time, one hour + 30 minutes per shift, so that the cleaning of 52,915.2 kg per year could be achieved and meeting an unsatisfied demand of 33.32% of the total. In the engineering of the project, it was defined the adequacy of the plant that will have the departments of management, production and sales, details the process or stages of the service and describes the functions and characteristics of the machinery, equipment and implements to be used in the company. The organizational study defines the legal and organizational structure, the company will be established under a limited liability company, will start with two partners and will be called "Magicalli clean" Company. Ltda. (Magically clean) and that will comply with all hierarchical levels and will have organizational charts and functions manual for each of the positions respectively. The economic study defined the fixed assets which amount to: 34,857.98 USD deferred assets: 2,329.44 USD and current assets 4,448.38 USD, which give an amount for the initial investment of 41,631.79 USD. The company intends to finance its initial investment with 75.98% of capital and 24.02% of capital with a loan in the Small Business Cooperative CACPE Yantzaza, at 21% annual interest, to quarterly installments for three years. According to the projected costs for the first year there is an amount of: 61,103.72 USD, which means that the unit cost of production is: 1.15 USD and adding a profit margin of 40% the price of serious sales Of 1.62 USD for the first year. With these results the income for the first year would be USD 85,545.21 and in the statement of income the net profit of USD 14,023.30 for year 1, thus calculating the break-even point for year 1 The Company must work at 64.54% of its installed capacity and sell an amount of 55,210.17 in its income. In the financial study, the financial ratios were applied with the purpose of ensuring the feasibility of the project, according to the projected cash flows, all positive, with 9.47% of the opportunity rate for the updating factor in The year 2016 you get a van of: 35,045.15 USD a benefit cost ratio of: 1.38 USD, a capital recovery period of: 1 year, 10 months and 6 days, a TIR of: 51.95% Sensitivity analysis with a 16.40% increase in cost results in a result lower than 1 which means that the company supports this increase. And with a decrease of 11.70% in your income also you get a result lower than 1 so the company is not sensitive to this decrease. As these ratios are all positive, it is verified that it is possible to implement the present project in the market. The conclusions are oriented to the results of the aforementioned studies and also the recommendations are an impulse to take into consideration the present work to implement it or to go to create other projects and ideas.